A 2001 Social Accounting Matrix for Zambia - International Food Policy Research Institute (International Food Policy Research Institute, 2005)
The Zambia Social Accounting Matrix (SAM) attempts to reflect the specific structure of the Zambian economy, by disaggregating the SAM's accounts across various activities, commodities, production factors, and households. At the macro level, the SAM is made to be consistent with the World Bank's 2001 Revised Minimum Standards Model (RMSM) of Zambia. At the micro level, the macro SAM was disaggregated using national and foreign trade accounts, and a variety of other sources. These included the 1998 Living Conditions Monitoring Survey (LCMS) and the input-output structure contained in the 1995 Zambia SAM, also produced by International Food Policy Research Institute (IFPRI).